Crisis Studies of The Discourse of Identity Politics in Indonesia from The Perspective of Asabiyah Ibn Khaldun - Pramono, Muhamad Fajar; Latief, Mohammad; Putri, Humaira Agam (Potret Pemikiran, 2023)
This paper critically analyzes Indonesia's discourse on identity politics through Ibn Khaldun's theory of asabiyah (social solidarity). It aims to diagnose issues surrounding the weaponization of identity for political ends that have polarized society and eroded unity. A qualitative approach scrutinizes empirical evidence on divisive identity politics before theoretically examining it via asabiyah. Recent history shows Indonesian identity politics exacerbating intergroup intolerance and discrimination by fracturing communities along ethnic and religious lines for power consolidation, violating asabiyah's emphasis on cohesion. However, moderate identity politics can enable democratic representation of societal diversity. Moving forward requires recalibrating identity discourse by fostering the unifying religious and nationalist solidarity underpinning asabiyah to balance inherent identity affiliations with preserving pluralistic national harmony.